2018
DOI: 10.1038/s41467-018-04408-0
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone is an endogenous regulator of BAFF and splenic B cell number

Abstract: Testosterone deficiency in men is associated with increased risk for autoimmunity and increased B cell numbers through unknown mechanisms. Here we show that testosterone regulates the cytokine BAFF, an essential survival factor for B cells. Male mice lacking the androgen receptor have increased splenic B cell numbers, serum BAFF levels and splenic Baff mRNA. Testosterone deficiency by castration causes expansion of BAFF-producing fibroblastic reticular cells (FRCs) in spleen, which may be coupled to lower sple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 62 publications
5
50
2
3
Order By: Relevance
“…Several observations suggest BAFF mediates the developmental effects of non-B cell ST6Gal-1. The bone marrow transplantation data showed a tendency toward male-specific in vivo differences in the IgD-/CD21- population upon loss of host ST6Gal-1, consistent with reported sex-associated variation in serum BAFF and the emerging role of sex hormones in the regulation of BAFF expression ( 46 , 70 , 71 ). ST6Gal-1-associated perturbations in early transitional B cells were observed in both bone marrow and splenic transitional compartments, consistent with the multi-stage significance of BAFF for immature B cells ( 72 , 73 ).…”
Section: Discussionsupporting
confidence: 85%
“…Several observations suggest BAFF mediates the developmental effects of non-B cell ST6Gal-1. The bone marrow transplantation data showed a tendency toward male-specific in vivo differences in the IgD-/CD21- population upon loss of host ST6Gal-1, consistent with reported sex-associated variation in serum BAFF and the emerging role of sex hormones in the regulation of BAFF expression ( 46 , 70 , 71 ). ST6Gal-1-associated perturbations in early transitional B cells were observed in both bone marrow and splenic transitional compartments, consistent with the multi-stage significance of BAFF for immature B cells ( 72 , 73 ).…”
Section: Discussionsupporting
confidence: 85%
“…4c). The enrichment of colocalizations in sex-specific tissues is consistent with established studies highlighting the strong sex bias and key role of sex hormones in autoimmunity [40][41][42] . Together, these results demonstrate that PICCOLO identifies genes that are likely specific to one trait category and in biologically relevant tissues.…”
supporting
confidence: 88%
“…With regard to androgens, they have previously found to regulate splenic B cells by suppressing their number both in male mice and men 27 . A more recent study also indicated, that androgens suppress the expression of BAFF cytokine in fibroblastic reticular cells (FRCs) in the spleen, and BAFF in turn, increases the number of the splenic B cells 28 .…”
Section: Discussionmentioning
confidence: 98%